2009
DOI: 10.1111/j.1399-3054.2009.01246.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a photoprotective function of low‐temperature‐induced anthocyanin accumulation in apple and pear peel

Abstract: The light requirement and low-temperature stimulation of anthocyanin synthesis in peel of apple (Malus domestica) and pears (Pyrus communis) and the presence of anthocyanins in immature fruits are not congruent with a visual function in dispersal. We hypothesized that anthocyanins afford photoprotection to peel during low-temperature-induced light stress and that the protection is not a fortuitous side-effect of light absorption by anthocyanin. The extent of photoinhibition at harvest and after light stress tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
65
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(75 citation statements)
references
References 60 publications
8
65
0
2
Order By: Relevance
“…Martinussen et al (2010) indicated that the total anthocyanins in bakeapple were negatively related to high temperature, similar to studies in apple and pear peel (Faragher 1983;Steyn et al 2009;Martinussen et al 2010). On the other hand, reports on anthocyanin content in pomegranate have shown decreasing anthocyanin content with rising temperature (Borochov-Neori et al 2011).…”
Section: Discussionsupporting
confidence: 49%
“…Martinussen et al (2010) indicated that the total anthocyanins in bakeapple were negatively related to high temperature, similar to studies in apple and pear peel (Faragher 1983;Steyn et al 2009;Martinussen et al 2010). On the other hand, reports on anthocyanin content in pomegranate have shown decreasing anthocyanin content with rising temperature (Borochov-Neori et al 2011).…”
Section: Discussionsupporting
confidence: 49%
“…They are widely distributed among the vascular plants, where they play important roles in photoprotection, plant-pollinator interactions, and responses to abiotic stress (Spaethe et al, 2001;Steyn et al, 2009;Schenke et al, 2011;Yuan et al, 2013). Variations in the spectral properties of different anthocyanins primarily arise from a small number of ring modifications on the chromophore itself, together with the combinatorial addition of peripheral moieties by various glycosyltransferases and acyltransferases (Mol et al, 1998).…”
mentioning
confidence: 99%
“…The metabolism of flavonoids follows a complex pathway, and some environmental factors such as temperature, water status, light condition, and nitrogen all have been demonstrated to affect flavonoids accumulation [22][23][24][25]. The present study demonstrated that lower temperature and to a lesser extent lower soil moisture content is favourable to flavonoid accumulation in Ginkgo leaves, and more specifically W2T1 and W3T1 treatments produced the highest total flavonoid content (Table 3).…”
Section: Discussionmentioning
confidence: 59%